(3ehQO GdUaG aj ehdO GdeUWai Udi Gddg Ydjg hSde (B/s - (3GHf YdGf, eMeO Ydj Hf eMeO YdGf Hf EHQGgjes 996-1057 (3gLQjs; (3GdedjHGQj, eMeO MHjH Hf eMeO GdYOfjs ((3YeGf (B:s (3ecJHI GdZGfe ddfTQ hGdJhRjY,s, 2022)
(3Hjf jOjc(B-(3CNj GdbGQF GdcQje(B-(3QSGdJGf aj SjQI GdfHj Udi Gddg Ydjg hSde ; GdChdi YfhGfgG (B(((3ehQO GdUaG aj ehdO GdeUWai Udi Gddg Ydjg hSde(B)) (3ddEeGe GdYdGeI GdeMOK eMeO Ydj Hf YdGf GdUqOjbj Gdecj (B((3J (B1057 (3g`(B)(3, hbO LeY gPG GdcJGH Ydi hLGRJg bUI GdehdO GdTQja HOkAG ef EQgGUGJ GdfSH GdTQja aGdMed aGdehdO eY GdYfGjI HEjQGO GdeHGMK GdTQYjI hGdfcGJ GdYdejI, hNJeg HHjGf Mce Yed GdehdO(B. (3hGdKGfjI YfhGfgG (B((3GdaLQ GdefjQ aj ehdO GdHTjQ GdfPjQ ddYdGeI Wg Hf eMeO Hf egfG GdLHQjfj (B((3J (B1178(3g`(B)(3, UOQgG HHjGf TQa GdehdO GdfHhj heG jJYdb Hg, hfGbT GdJaVjd Hjf djdI GdehdO GdfHhj hHjf djdI GdbOQ, eY SQO ehLR dCge GdahGFO GdYdejI GdeJYdbI HehdOg Udi Gddg Ydjg hSde hQVGYg aj Hfj SYO, hCfgGgG HPcQ MGOKI Tb UOQg GdTQja Ydjg GdUdGI hGdSdGe, hbO NJe GdcJGHGf HLedI ef GdagGQS GdYdejI JjSjQG ddhUhd Edi ahGFOgeG(B.s
(3HHdjhLQGajI (B: (3UaMI (B227-229.s
Keywords: (3eMeO (B((3Udi Gddg Ydjg hSde(B)s -- 53 (3bHd GdgLQI(B-11 (3gLQjs; (3GdSjQI GdfHhjIs -- (3ehdO GdfHj Udi Gddg Ydjg hSdes; (3GdSjQI GdfHhjIs